Please don’t leave me - separation anxiety and related traits in borderline personality disorder - Matthies, Swantje; Schiele, Miriam A.; Koentges, Christa; Pini, Stefano; Schmahl, Christian; Domschke, Katharina (Current psychiatry reports, 2018)
Purpose of ReviewIn light of the apparent symptomatic resemblance of separation anxiety disorder (SAD) symptoms on the one hand and abandonment fears, anxiousness, and separation insecurity central to borderline personality disorder (BPD) on the other hand, a comprehensive overview of separation anxiety and related traits in BPD is provided.Recent FindingsEpidemiological, environmental, psychological, and neurobiological data connecting BPD to separation events, feelings of loneliness, insecure attachment styles, dimensional separation anxiety as well as SAD per se suggest a partly shared etiological pathway model underlying BPD and SAD. Differential diagnostic aspects and implications for treatment are discussed, highlighting separation anxiety as a promising transdiagnostic target for specific psychotherapeutic and pharmacological treatment approaches in BPD.SummaryThis innovative angle on cross-disorder symptomatology might carry potential for novel preventive and therapeutic avenues in clinical practice by guiding the development of interventions specifically targeting separation anxiety and attachment-related issues in BPD.
First online: 28 August 2018
Gesehen am 16.10.2019